1997
DOI: 10.2307/3433897
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Mouse Liver Tumor Formation for Carcinogenic Risk Assessment: Results and Conclusions from a Survey of Ten Years of Testing by the Agrochemical Industry

Abstract: A survey was performed on the results of 138 carcinogenkicty studies conducted in various mouse strins by the agrochemical industry over the period [1983][1984][1985][1986][1987][1988][1989][1990][1991][1992][1993]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…In a retrospective examination of data from 138 carcinogenicity studies in mice, increased liver weight at twelve months was typically associated with development of liver tumor by eighteen to twenty-four months (Carmichael et al 1997). An increased liver weight of 110% at one year was not associated with liver tumorigenesis, whereas liver tumorigenicity was seen if the one-year liver weight was 150% of control values (Carmichael et al 1997). A similar correlation between liver weight at fifty-two weeks and ultimate hepatocarcinogenicity in mice was reported by scientists at the NTP (Haseman et al 1997).…”
Section: Liver Enlargement and Hepatocarcinogenicitymentioning
confidence: 99%
“…In a retrospective examination of data from 138 carcinogenicity studies in mice, increased liver weight at twelve months was typically associated with development of liver tumor by eighteen to twenty-four months (Carmichael et al 1997). An increased liver weight of 110% at one year was not associated with liver tumorigenesis, whereas liver tumorigenicity was seen if the one-year liver weight was 150% of control values (Carmichael et al 1997). A similar correlation between liver weight at fifty-two weeks and ultimate hepatocarcinogenicity in mice was reported by scientists at the NTP (Haseman et al 1997).…”
Section: Liver Enlargement and Hepatocarcinogenicitymentioning
confidence: 99%
“…In contrast, PB is a well-known potent inducer of hepatic xenobiotic metabolizing oxidative enzymes, which results in a pronounced hepatocellular hypertrophy and ultimately in liver tumor formation in rodents (Carthew, Edwards, and Nolan 1998). The strong induction of enzymes is believed to play a part in the mechanism of rodent liver tumorigenesis by PB and similar enzyme-inducing agents (Carmichael et al 1997).…”
mentioning
confidence: 99%
“…Increases in LWs have been examined for relationships with liver tumor risk in 2-year carcinogenicity studies in rodents. 14,36 In a survey of 138 agrochemicals examined in mice, a relative increase in LW of ≥150% of control values after 1 year of treatment was positively correlated with the induction of liver tumors at 2 years. 36 The average relative LW of top dose animals in negative studies of 110% of control 36 was similar to our threshold of 117%.…”
Section: Resultsmentioning
confidence: 99%
“…14,36 In a survey of 138 agrochemicals examined in mice, a relative increase in LW of ≥150% of control values after 1 year of treatment was positively correlated with the induction of liver tumors at 2 years. 36 The average relative LW of top dose animals in negative studies of 110% of control 36 was similar to our threshold of 117%. In a survey of mouse and rat NTP studies examining correlations between LW and/or histological parameters and carcinogenesis, Allen et al 14 found that hepatocellular hypertrophy was the best single predictor of liver cancer in mice.…”
Section: Resultsmentioning
confidence: 99%